Update on the clinical utility of once-daily tacrolimus in the management of transplantation - Revollo J (Dove Medical Press, 2015)
Jane Revollo Department of Pharmacy, Jackson Memorial Hospital, University of Miami Leonard M Miller School of Medicine Miami, FL, USAThe review by Posadas Salas and Srinivas of the clinical utility of once-daily tacrolimus formulations in the management of transplant patients1 was timely and relevant. It is worth noting, however, the data were presented in a way that overlooked several key differences between two distinct once-daily tacrolimus formulations. These formulations differ in bioavailability, Cmax, Tmax, dose required to achieve target trough levels, and time to reach target trough. The specific formulation and dosing information of one product was detailed in this review (described as modified release 4 [MR-4]; Astagraf®, Astellas Pharma Inc., Tokyo, Japan), but no formulation or dosing details were provided for a very different once-daily tacrolimus formulation (LCP-Tacro™; Veloxis Pharmaceuticals A/S, Hørsholm, Denmark) for which a thorough review was recently published.2 The latter product is currently approved in Europe and under review by the US Food and Drug Administration in the US. In presenting data in this review, the authors did not identify which product was investigated in each of the studies discussed. This could easily lead to misinterpretation of results or erroneous conclusions, ie, that both once-daily formulations are the same. In fact, a careful parsing of the data clearly demonstrates that they are not equivalent. Misunderstanding of this point could have a potentially serious impact on appropriate dosing, safety, and patient management in the post-transplant setting. Differentiation between the two products is needed to clarify what appear to be conflicting results of the studies presented in this review.View original paper by Posadas Salas and Srinivas